Alterations in niban gene expression as a response to stress conditions in 3T3-L1 adipocytes - SÜSLEYİCİ, BELGİN (SPRINGER, 2020)
Adipocyte death is important in obesity development. Understanding and prevention of adipocyte deaths may be a molecular approach in the treatment. In the study, we aimed to understand role of Niban gene, which acts as an anti-apoptotic molecule as a response to stress conditions, in adipocytes. 3T3-L1 adipocytes were treated with different doses of linoleic acid, hydrogen peroxide and ethanol; and proliferation of the cells examined with real time monitoring iCELLingence system. Gene expression levels were measured by q-PCR. As a response to 24h 480 mu M linoleic acid treatment, Niban gene expression was found to be higher than control group (p = 0.008), whereas 24 h 90 mM ethanol treatment was determined to be lower than control group (p = 0.008). The highest value of Niban gene expression among H2O2 treatment groups was detected in 4h 600 mu M H2O2 in comparison to control group (p = 0.008). To understand role of Niban in adipogenesis, Niban gene expressions were compared between pre-adipocytes and advanced fat accumulated adipocytes and determined to be significantly different (p = 0.042). Our results suggest that Niban might be involved in stress response process in adipocytes. However, the exact molecular role of Niban needs to be investigated in further studies.
Keywords: Niban; Linoleic acid; Cell stress; Obesity; Adipogenesis; CONJUGATED LINOLEIC-ACID; ENDOPLASMIC-RETICULUM STRESS; ADIPOSE-TISSUE; INSULIN-RESISTANCE; ER STRESS; OBESITY; APOPTOSIS; TRANS-10; CIS-12; CELLS